Relationship between Body Image, Body Mass Index and Self Esteem among Obese and Non Obese Female Adolescents - Majeed, Moomal (Annals of Human and Social Sciences, 2023)
Purpose of this research was to study the relationship between body mass index, body image dissatisfaction and self-esteem among obese and normal weight female adolescents in district Attock. This research also aimed to study differences among obese and non-obese female adolescents on self-esteem and body image. The population of study was female adolescents. Sampling technique used for selection of sampling was purposive sampling. Sample size of this research was 200 female adolescents. Survey method was used to collect data from sample. Statistical Package for Social Science (SPSS) software was used for obtaining results of this study. Finding of this study shows that there is significant positive correlation between body image dissatisfaction and body mass index. It indicates a significant negative correlation among body mass index, self-esteem and body image dissatisfaction. Results of this research indicate that obese female adolescents have more body image dissatisfaction and low self-esteem as compared to non-obese female adolescents.